A salutogenic urban design framework: the case of UK local high streets and older people. (26th October 2022) - Brunelli, Luca; Smith, Harry; Woolrych, Ryan
Summary: The article provides a novel look at the links between salutogenesis, health promotion, and urban design supported by the findings of recent research on local high streets and their benefits for the well-being of older people. Salutogenesis and the related explanatory concept of sense of coherence (SOC) have provided a theoretical framework for developing healthy settings interventions, shifting the focus from exploring barriers and deficits to assets and resources in promoting people's health and well-being. While these concepts have informed policies and programmes at the level of regions and cities, no attempt has been made to establish more direct links with the disciplines devoted to the organization and design of the built environment at the scale of public spaces and streets. This article advances the idea that the main categories of SOC—comprehensibility, manageability and meaningfulness—have found application in urban design theory. Linking these categories with urban design concepts in a comprehensive framework, it is possible to guide interventions aimed at strenghtening well-being resources available in the public realm. This is corroborated by the findings resulting from a study of the well-being experiences of older people ( n = 84) across a range of local high streets in the city of Edinburgh (UK) applying an innovative multi-methods approach. The discussion establishes the links between well-being benefits, SOC constructs and urban design concepts, and underscores the potential of the proposed framework to guide a design-oriented salutogenic approach to the built environment. Lay Summary: In this article, we propose a novel conceptual framework that links health promotion and the theory of salutogenesis with key concepts commonly used in the urban design. The framework is articulated in relation to the findings of recent research on main neighbourhood commercial streets in Edinburgh (UK)—local high streets—and their benefits for the well-being of older people. Salutogenesis theory and related concepts have emphasized the role that everyday environments can have in promoting people's health and well-being, through the opportunities for social interaction and access to material resources they provide. They have informed policies and programmes at city-wide level but not at the scale of streets and public spaces, which is the spatial domain of urban design. The proposed framework establishes the links for a design-oriented salutogenic approach to the built environment and suggests a range of interventions in local high streets that can benefit an ageing population.